On the relationship between fire regime and vegetation structure in the tropics - Veenendaal, E; Torello-Raventos, M; Miranda, H; Sato, N; Oliveras-Menor, I; van Langevelde, F; Asner, G; Lloyd, J (Wiley, 2018)
We assessed data from 11 experiments examining the effects of the timing and/or frequency of fire on tropical forest and/or savanna vegetation structure over one decade or more. The initial ‘control treatment’ in many such cases consisted of previously cleared land. This is as opposed to natural vegetation subject to some sort of endogenous fire regime before the imposition of fire treatments. Effects of fire on fractional foliar cover are up to 10-fold greater when clearing pre-treatments are imposed. Moreover, because many of the ‘classic’ fire trials were initialised with applied management questions in mind, most have also used burning regimes much more frequent and/or severe than those occurring in the absence of human activity. Once these factors are taken into account, our modelling analysis shows that nonanthropogenic fire regimes serve to reduce canopy vegetative cover to a much lower extent than has previously been argued to be the case.  These results call into question the notion that fire effects on tropical vegetation can be of a sufficient magnitude to maintain open-type savanna ecosystems under climatic/soil regimes otherwise sufficient to give rise to a more luxurious forest-type vegetation cover.